ANALISIS KURIKULUM KHAS DI SMPIT IBNU KHALDUN CIREBON - Nasrulloh, Iman; Andiani, Fini; Fauziah, Kamela; Ispiyani, Syipa (Ridwan Institute, 2023)
The main objective of the curriculum is to impress graduates who are religious, characteristic, and superior in digital technology. SMPIT Ibnu Khaldun implemented eight daily pre-KBM activities, including religious activities, literacy, and teaching guidance. They also have extracurricular in various fields. The applied learning model is Project Based Learning, where students must produce a project or work related to the subject at the end of the semester. This research uses qualitative methods with data collection from primary and secondary sources, including interviews, observations, and documentation. The results of the research showed that the typical curriculum at SMPIT Ibnu Khaldun is able to impress graduates with good soft skills, hard skills, and spiritual skills. Thus, SMPIT Ibnu Khaldun has successfully integrated religious education, character, and digital technology into their curricula, with a focus on project-based learning. It has a huge potential to impress outstanding and qualified graduates.